Early Detection and Screening of Pancreatic Cancer - Gonda, Tamas A; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
No abstract available. Image: Columbia University's New Transparent Medical Center. New York, NY, USA.